Extend of Skipped Multifocal Noncontiguous Spinal Tuberculosis Beyond Imagination: A Rare Case Report and Literature Review - Sonawane, Dhiraj Vithal (Asian J Neurosurg, 2020)
Skipped multifocal extensive spinal tuberculosis involving the whole spine is very rare, which presents with atypical presentations and imaging features. So far, only five cases have been reported. Most of these patients have only two noncontiguous lesions. We are reporting a case of an 18-year-old boy with noncontiguous multifocal spinal tuberculosis involving cervical, thoracic, thoracolumbar, and lumbar segments. The patient was treated with antituberculous drug therapy and was operated for thoracolumbar spinal lesion. He made an excellent recovery. The possibility of tuberculosis is considered for any skip lesions involving the spine cautiously. Careful physical examination, trials of antitubercular therapy, and using the whole spine magnetic resonance imaging routinely also play an important role in the diagnosis and treatment of this disease. In patients with noncontiguous spinal involvement, there is a high percentage of requirement of surgical treatment due to fulminant behavior of the disease in these patients.